Contributions to the ecological study of summer ornithofauna the park "La Izvor", the Sculeni Barrier, Chisinau - CÎRLIG, Tatiana; CÎRLIG, Natalia (Acta et Commentationes Exact and Natural Sciences, 2020)
The research of the urban ornithofauna was carried out within the institutional project, ,, The study of anthropogenic action on biodiversity, the physiological status of population Chisinau and the use of results in the formation of transdisciplinary competences in the educational process" carried out during the period 2015-2019. In the result of the research, 64 species of birds belonging to 12 orders were identified. The most numerous being the Passeriformes order. In most its ornithofauna the park is presented by omnivorous and insectivorous forms. From a frequency point of view these are common and frequency species.